Hubungan Asupan Zat Gizi Mikro dan Komposisi Lemak Tubuh dengan Tingkat Kebugaran Mahasiswa di UKM Sepakbola UNY - Sukmajati, Refiana Putri; , Dwi Sarbini, S.ST., M.Kes; , Fitriana Mustikaningrum, S.Gz, M.Sc (2015)
Colleges student needful fitness for learned, college, oractivities supportive activity lecturing and on this age happening processes growth and tall activity. One of factor which regard fitness is nutrient intake (micro nutrient substance) and nutrient state (body fat composition). Football sport is sporting one charge optimal body fitness. The research to analyzed the correlations between micro nutrient intake and body fat compositionwith the college student's level ofphysical fitness at Yogyakarta State University football club. This observational type is crossectional. The data of the micro nutrient substance is collected by food recall 4x24 hour not serially, the data of the body fat composition is collected by undertaking measurement utilizes tool Bioelectrical Impedance Analyzer ( BIA ), and the data of the physical fitness is collected through measurement by bleeptest method. The total subject research is 36 person that taken by simple random sampling. Statistical quiz that is utilized for analyzed correlation is test correlation of Pearson Product Moment and Rank Spearman test. The results shows most of the research subject have micro nutrient substance that insufficiently, the intake of vitamin B1 as big as 97,2%, the intake of vitamin B6 as big as 58,3%, the intake of vitamin C as big as 94,4%, and the intake of iron substance as big as 52,8%. The research subject that have moderate body fat composition as big as 80,6%. The research subject that have enough category of physical fitness as big as 41,7%. Result tests correlation among intake of vitamin B1 with fitness is p=0,799, intake of vitamin B6 with fitness is p=0,682, intake of vitamin C with fitness is p=0,869, intake of iron substance with fitness is p=0,042, and body fat composition with fitness is p=0,004. There was no correlation among intake of vitamin B1, vitamin B6, and vitamin C with the college student's level of physical fitness at Yogyakarta State University football club. There is a correlation among iron substance intake and body fat composition with the college student's level of physical fitness at Yogyakarta State University football club.